Social Changes Through the Encounter of Countries in Southeast Asia: A Historiy-Hermeneutics Through the Contacts of Chinese and the People of Maluku in Spices Trading - Hetharion, Bety D.S. (TAWARIKH, 2010)
ABSTRACT: Historical interpretation must look for what people did on their historical circle. On one hand, history hermeneuitcs is an effort to understand peopleâs self-knowledge that what people know is a truth or a reality from their own worldview. On the other hand, history hermeneutics tries to make a new perspective that what happen now is unseparable from past. This is why hermeneutics of history might be used to makeÂ  an interpretation about the truth itself. Based on history hermeneutics, I try to make an analysis about Chinese and Moluccans contact during spices trade period. This study based on social changes in Maluku on economic and social life. I want to study the mutual economic model by Asian, something different with economic model by European which so politically.KEY WORDS: history hermeneutics, social changes, interpretation and understanding, and Chinese and Moluccans relations in Maluku.About the Author: Bety D.S. Hetharion, M.Pd. is a Lecturer and currently as Head of Department of History Education, Faculty of Teacher Training and Educational Sciences UNPATTI (University of Pattimura) in Ambon, Maluku, Indonesia. She can be reached at: hetharionb@yahoo.comHow to cite this article? Hetharion, Bety D.S. (2010). âSocial Changes Through the Encounter of Countries in Southeast Asia: AÂ  Historiy-Hermeneutics Through the Contacts of Chinese and the People of Maluku in Spices Tradingâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.159-168. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 5, 2010); Revised (March 9, 2010); and Published (April 28, 2010).